The Influence of Solvents on the Liquid-Phase Adsorption Rate of n-Hexane in 5A Molecular Sieves - Cao Jun; Shen Benxian (Adsorption Science & Technology)
The main branched hydrocarbons in naphtha are isomeric hydrocarbons, cyclo-paraffins and aromatics. The naphthenic base naphtha has a high content of cyclo-paraffins while aryl naphtha has a correspondingly high content of aromatics. The work described in this paper investigates the influence of each type of principal branched hydrocarbon in naphtha on the adsorption kinetics of n-hexane in 5A molecular sieves at 283 K, 303 K and 323 K, respectively. The results obtained indicate that the effect of the solvent on the adsorption rate decreased in the sequence toluene > methyl cyclohexane > iso-octane. The apparent diffusivity coefficients and the apparent diffusional activation energies for the adsorption of n-hexane in 5A molecular sieves in the presence of different solvents were obtained by fitting the data to the kinetic model and the Arrhenius expression. The results indicate that the paraffin base naphtha is the most suitable feed for the adsorption separation of n-paraffins from branched hydrocarbons employing 5A molecular sieves. The kinetic data could also help to predict the adsorption behaviour in the adsorption bed when different kinds of naphtha are employed as the feed.